TEST OF FIVE CLONES OF POTATO (Solanum tuberosum) PPPT6 LINE ON GROWTH, RESULTS AND MORPHHOLOGICAL CHARACTERIZATION - ninda firdausi; Nurhidayati Nurhidayati; Abdul Basit (AGRONISMA, 2022)
This study aims to examine seven potato germplasm in Indonesia with three comparisons (Granola, Atlantic, and South Sulawesi). It is hoped that the genotypes from the characterization test will fulfill the main requirements for the description of the variety so that the registration of varieties can be carried out in the end. The research was carried out in Jurang Kuali Hamlet, Sumber Brantas Village, Bumiaji District, Batu City. This experiment used a simple randomized block design (RAK) with clone treatment consisting of five levels: P1 (PPT6 clone No. 1); P2 (PPT6 clone No.2); P3 (PPT6 clone No.3); P4 (PPT6 clone No.4); P5 (PPT6 clone No.5). Each treatment was repeated 3 times using 3 samples for observation. Variables observed were growth variables which included: plant height, stem diameter, number of stems, number of leaves, and leaf area, tuber length and tuber diameter; and production variables which include: tuber weight per plant, tuber weight per mound, and tuber weight per hectare. Data from the experimental results were analyzed using analysis of variance (ANOVA, F test) with a level of 5% to determine the effect of treatment if there was a significant effect of treatment followed by a further test of BNT with a level of 5%. The results of this study indicated that the best potato crop growth was found in the PPPT6 potato clone No.2 and the PPPT6 potato clone No.5, and the best potato crop yield was found in the PPPT6 potato clone No.2. In plain view, the potato clone PPPT6 No.2 was bigger than the other plants. This is due to the fulfillment of the need for nutrients that can be absorbed directly by the roots of potato plants without spreading and competing with other plants. So it has a good plant height, stem diameter, number of stems, number of leaves, and leaf area. According to Zelelew (2016), taller plants will have more leaf production per plant and will affect the production of photosynthesis.